Maturity alters drop vertical jump landing force-time profiles but not performance outcomes in adolescent females - Pedley, J. S.; DiCesare, C. A.; Lloyd, R. S.; Oliver, J. L.; Ford, K. R.; Hewett, T. E.; Myer (Scandinavian Journal of Medicine & Science in Sports, 2021)
The stretch-shortening cycle (SSC) assists in effective force attenuation upon landing and augments force generation at take-off during a drop vertical jump (DVJ). General performance outcomes such as jump height or peak measures have been used to assess SSC function in youth populations; however, these discrete metrics fail to provide insight into temporal jump-landing characteristics. This study assessed DVJ force-time profiles in 1013 middle and high-school female athletes (n = 279 prepubertal, n = 401 pubertal, and n = 333 postpubertal). Maturity status was determined using the Pubertal Maturation Observation Scale. Ground reaction force data were analyzed to extract a range of variables to characterize force-time profiles. SSC function was categorized as poor, moderate, or good dependent on the presence of an impact peak and spring-like behavior. No differences in jump height or ground contact time were observed between maturity groups (p > 0.05). Significant differences in absolute peak landing and take-off force were evident between all maturational statuses (p < 0.05). Relative to bodyweight normalized forces, only peak take-off force was significantly different between prepubertal and postpubertal groups (p < 0.05; d = 0.22). Spring-like behavior showed small improvements from pubertal to postpubertal (p < 0.05; d = 0.25). Most females displayed poor SSC function at prepubertal (79.6%), pubertal (77.3%), and postpubertal (65.5%) stages of maturity. Large increases in absolute forces occur throughout maturation in female athletes; however, only small maturational differences were found in relative force or spring-like behavior. Consequently, most girls display poor SSC function irrespective of maturity.